TEACHING NURSING STAFF TO MINIMIZE BEHAVIORS AND OPTIMIZE FUNCTION FOR NURSING HOME RESIDENTS WITH DEMENTIA. (11th November 2018) - Galik, E; Resnick, B; Vigne, E; Holmes, S D
Abstract: Residents with moderate to severe cognitive impairment who live in nursing homes frequently exhibit resistiveness to care during activities of daily living and have limited opportunity to engage in physical and functional activities. To minimize behavioral symptoms and increase time spent in physical activity, the Function and Behavior Focused Care (FBFC) intervention was implemented over 12 months with nursing staff at 6 nursing homes in Maryland. A total of 254 staff was educated about FBFC, and they scored 97% on the FBFC knowledge test. There was evidence that the nurses provided more function and behavior focused care for residents over the course of the study. At four months 5.00 (SD=3.16) out of 19 care interactions provided function focused care and at 12 months 5.44 (SD=3.12) out of 19 care interactions provided function focused care. This study provides some evidence that nursing staff can learn and incorporate FBFC into routine care.